Feasibility of 3D-printed models of the proximal femur to real bone: a cadaveric study. Issue 4 (July 2019) - Sallent, Andrea; Seijas, Roberto; Pérez-Bellmunt, Albert; Oliva, Eulalia; Casasayas, Oriol; Escalona, Carles; Ares, Oscar
Introduction: 3D technology has increased popularity during the past decade due to recent advancements and has been described as a useful tool in several fields of medicine including orthopaedic surgery. Applications include preoperative planning, custom-made implants, patient-specific guides, etc. The aim of this study was to evaluate the similarity between 3D-printed models and cadaveric femoral heads, based on CT scans. Methods: Cadaveric study of 12 male hips. Computed tomography (CT) was performed and through a semi-automatic segmentation process created the 3D model. Using a 3D printer, the model was printed in ABS plastic. 1 observer performed several measurements in the cadaver, and a 2nd observer performed the same measurements in the 3D-printed model. A 3rd observer compared both measurements and performed the statistical analysis. Results: There were no significant differences in the measurements of bony structures between the cadaveric specimens and the 3D-printed model ( p > 0.05 in all cases). We found significant differences when comparing measurements containing a soft tissue element, for example the dimensions of the cartilage covered femoral head ( p < 0.0001). Conclusions: 3D-printed models of the hip are accurate and feasible to the real bone and can thus be reliable for preoperative planning or other uses that may arise in orthopaedic surgery. Presence of cartilage must be considered when creating the 3D model from CT that considers bone but not cartilage.